Detoxification of Deoxynivalenol via Glycosylation Represents Novel Insights on Antagonistic Activities of Trichoderma when Confronted with Fusarium graminearum - Ye Tian; Yanglan Tan; Na Liu; Zheng Yan; Yucai Liao; Jie Chen; Sarah de Saeger; Hua Yang; Qiaoyan Zhang; Aibo Wu (Toxins, 2016)
Deoxynivalenol (DON) is a mycotoxin mainly produced by the Fusarium graminearum complex, which are important phytopathogens that can infect crops and lead to a serious disease called Fusarium head blight (FHB). As the most common B type trichothecene mycotoxin, DON has toxic effects on animals and humans, which poses a risk to food security. Thus, efforts have been devoted to control DON contamination in different ways. Management of DON production by Trichoderma strains as a biological control-based strategy has drawn great attention recently. In our study, eight selected Trichoderma strains were evaluated for their antagonistic activities on F. graminearum by dual culture on potato dextrose agar (PDA) medium. As potential antagonists, Trichoderma strains showed prominent inhibitory effects on mycelial growth and mycotoxin production of F. graminearum. In addition, the modified mycotoxin deoxynivalenol-3-glucoside (D3G), which was once regarded as a detoxification product of DON in plant defense, was detected when Trichoderma were confronted with F. graminearum. The occurrence of D3G in F. graminearum and Trichoderma interaction was reported for the first time, and these findings provide evidence that Trichoderma strains possess a self-protection mechanism as plants to detoxify DON into D3G when competing with F. graminearum.